A comprehensive guide to the Argentinian case-bearer beetle fauna (Coleoptera: Chrysomelidae: Camptosomata) - Agrain, Federico Alejandro (2017)
Knowledge of Argentinian Camptosomata has largely remained static for the last 60 years since the last publication by Francisco de Asis Monrós in the 1950’s. One hundred and ninety Camptosomata species (182 Cryptocephalinae and 8 Lamprosomatinae) in 31 genera are recorded herein from Argentina. Illustrated diagnostic keys to the subfamilies, tribes, subtribes and genera of Argentinian Camptosomata, plus species checklists and illustrations for all genera of camptosomatan beetles cited for each political region of Argentina are provided. General notes on the taxonomy and distribution, as well as basic statistics, are also included. This study provides basic information about the Camptosomata fauna in Argentina that will facilitate in the accurate generic-level identification of this group and aid subsequent taxonomic revisions, and phylogenetic, ecological, and biogeographic studies. This information will also facilitate faunistic comparisons between neighboring countries. Two nomenclatural acts are proposed: Temnodachrys (Temnodachrys) argentina (Guérin, 1952), comb. n., and Metallactus bivitticollis (Jacoby, 1907), comb. n. The following are new records for Argentina: Stegnocephala xanthopyga (Suffrian, 1863) and Lamprosoma azureum Germar, 1824. Currently, the most diverse camptosomate tribe in Argentina is Clytrini, with almost twice the number of species of Cryptocephalini. New records for Argentina are predicted.